Estrutura biopolimérica bicamada obtida por casting e electrospinning aditivada com extrato natural de casca de jabuticaba - Avila, Luisa Bataglin (2024)
The present work aims to produce and characterize bilayer membranes, with potential use as active food packaging, obtained through electrospinning and casting techniques, using zein and chitosan biopolymers as matrices and jaboticaba epicarp extract (JEE) as a natural additive. The JEE was obtained by maceration, characterized and lyophilized for later use as a natural additive in membrane formulation. Thus, the first step of the research provided the development of bilayer membranes in chitosan/zein configuration with JEE additives for application as active food packaging. The membranes were characterized by thickness, solubility in water, water vapor permeability and fibres mean diameter. The results showed that the addition of a second layer improved the barrier properties of the material when compared to the monolayer zein fiber. Furthermore, the thermal stability of the membranes was improved by the addition of JEE in the biopolymeric matrix and the presence of JEE could be confirmed through FTIR spectra. Active potential of the material was confirmed by antimicrobial analysis since the bilayer membrane with JEE showed inhibition halos against E. coli and S. aureus microorganisms. The second step of the research aims to explore the potential application of this material within a specific food sector. In this sense, bilayer membranes in the same previous configuration, chitosan/zein with and without addition of lyoph ilized JEE, were evaluated both for the properties described previously and for the mechanical properties and wettability of the chitosan film in relation to zein solutions. To determine the most suitable food classification for the type of active packaging material developed, the release capacity of bioactive compounds in terms of total phenolic and antioxidant activity in different food simulants was evaluated. The results showed that addition of extract improved adhesion between the layers, a fact observed by the hydrophilic character of the chitosan film compared to the zein solutions. Furthermore, thermal stability analysis also confirmed the good compatibility between the biopolymers. Through FTIR analysis it was possible to identify functional groups characteristic of membrane components. The active potential of the bilayer membrane added with natural extract was proven through a migration test of bioactive compounds in a food simulant. The best results for migration of phenolic compounds and antioxidant activity were observed in oil, with antimicrobial potential also observed in this fluid against the microorganisms E. coli and S. aureus. The present study highlights the potential of using different biopolymers to produce packaging materials. Furthermore, the benefits of using agro-industrial residue, such as jaboticaba epicarp, as a source of bioactive compounds are also highlighted. Therefore, the development of bilayer biopolymeric structures combined with the use of natural additives is a promising strategy for application as active food packaging, especially fatty foods, minimizing losses due to oxidation and microbial contamination.